Capturing blast impact on helmets - Bloodworth-Race, Susie (Cranfield University, 2020)
When shielded from the fireball and fragmentation of an explosion, the blastwave can still cause multiple injuries, with increasing prevalence of Traumatic Brain Injury (TBI) noticed amongst survivors. Relatively low peak overpressures can result in Blast-Induced Mild TBI (bTBI), with significant deterioration in mental health manifesting as anxiety, behavioural changes, even loss of fine motor control, symptoms which can often be confused with Post Traumatic Stress Disorder (PTSD).The image shows a helmet blast impact from a compressed air shocktube, the resulting movement of head and helmet captured with high speed video. The moment of impact can be seen in the top sector with the shockwave captured as a vertical band of compressed air just behind the front of the head. The helmet is lifted, rotated backwards, held by the chinstrap and bounced back down onto the head, resulting in multiple possible mechanisms for bTBI.
Keywords: 'DSDS20 Digital Image'; 'DSDS20'; 'Helmet'; 'Blast'; 'Traumatic Brain Injury (TBI)'; 'Physical Sciences not elsewhere classified'